How Does Students’ Knowledge About Information-Seeking Improve Their Behavior in Solving Information Problems? - Marioleni Parissi, Vassilis Komis, Gabriel Dumouchel, Konstantinos Lavidas, Stamatios Papadakis (Educational Process: International Journal)
Background/purpose – This study investigates how the teaching intervention and familiarity with the search topic enhance Greek students’ behavior while solving information problems.